The rhetoric of explanation in Lucretius' De rerum natura - Marković, Daniel. (Mnemosyne, Supplements, 2008)
Alleged incompatibility of Epicurus' philosophy with rhetoric has led modern scholars to isolate rhetorical procedures in Lucretius' De rerum natura and regard them as non-Epicurean, accessory features. This study of Lucretius' rhetorical procedures is based on a wider understanding of the term rhetoric, not limited to the genre of oratory. In a fresh discussion of the questions of provenance and the role of the most important formal procedures of exposition in De rerum natura the author argues that instead of injecting rhetorical strategies from non-Epicurean sources, Lucretius in fact intensified rhetorical elements already present in the work of Epicurus. These elements are used for the purpose of explanation, and function as cognitive and mnemonic aids for the reader.